Pengaruh Pembelajaran Kooperatif Tipe Numbered Head Together Terhadap Kemampuan Pemecahan Masalah Matematis dan Kemandirian Belajar - Dina Novarina Perdana (Jurnal Ilmiah Pendidikan Scholastic, 2022)
This research is motivated by the lack of mathematical problem solving skills and self regulated learning class XI science student MAN Kabupaten Solok. To overcome this problem use cooperative learning model NHT. The purpose of this study was to determine the effect of the application of cooperative learning model NHT to mathematical problem-solving ability and self regulated learning of class XI science student learning MAN Kabupaten Solok. This research is a quasi experiment. The population in this study were all students of class XI Science MAN Kabupaten Solok. The samples in this study were students of class XI IPA 3 MAN Koto Baru Solok as the experimental class and the students of class XI IPA 2 MAN Koto Baru Solok as the control class. Data were obtained from the results of the initial test and final test capabilities in the form of mathematical problem solving questions and a questionnaire to see students self regulated learning. Data analysis was performed using t-test, t 'and Mann Whitney U test The results of data analysis indicate that: 1) the ability of problem solving and self regulated learning matetamtis student learning using cooperative learning model NHT higher than students who are learning using conventional learning 2) mathematical problem solving skills and self regulated learning mathematics students who have a high initial ability learning using cooperative learning model NHT higher than students whose learning using conventional learning 3) mathematical problem solving skills and self regulated learning mathematics students who have low initial learning capability using cooperative learning model NHT higher than students who are learning using conventional learning.